Media and Politics: Re-Thinking the Indonesian Broadcasting System - Masduki Masduki (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2017)
The emergence of the policy of broadcasting liberalization in the established democracies of Europe and North America, which is indicated by the absence of state intervention to broadcasting governance has been influencing broadcasting policy in the new democracies, including Indonesia. Is it true that Indonesia adopts a liberal broadcasting policy? This paper outlines two issues. First, the academic debate surrounding broadcasting system in the world. Second, discussion as stated by scholars on a thesis of the enactment of the liberal media system in Indonesia that is primarily based on the broadcasting policies after Suharto’s reign of power, among others Law 32/2002 on Broadcasting. Based on the intensive literature review, it can be concluded that the broadcasting system prevailing in Indonesia is not purely liberal, but a mix of liberal and authoritarian model, a unique character that also occurs in the post-communist and post-authoritarian states in Asia, Africa and Eastern Europe. This mix is indicated within the last fifteen years through the adoption of public and community broadcasters and the establishment of Komisi Penyiaran Indonesia (KPI) as an independent regulator that were accompanied with the existing control of the ruling government to public broadcasters (RRI & TVRI); the weak mandate of KPI and the omission of commercial broadcasting domination.